2016
DOI: 10.1136/jnnp-2016-313246
|View full text |Cite
|
Sign up to set email alerts
|

Early blood pressure lowering in patients with intracerebral haemorrhage and prior use of antithrombotic agents: pooled analysis of the INTERACT studies

Abstract: NCT00226096, NCT00716079.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In addition, as not all ICH patients can benefit from intensive SBP lowering, it is necessary to select subgroups of patients at high risk of developing HE. Actually, studies have shown that those ICH patients who presents with an early onset, higher initial SBP, prior anti-thrombotic therapy, or milder neurological dysfunction at baseline were found to be associated with better functional outcomes in rapid SBP lowering (114,125,126). However, currently the characteristics of ICH patients benefiting from SBP control are still unclear and a complete screening scheme should be established to facilitate clinical practice in future studies.…”
Section: Intensive Blood Pressure-lowering Treatmentmentioning
confidence: 99%
“…In addition, as not all ICH patients can benefit from intensive SBP lowering, it is necessary to select subgroups of patients at high risk of developing HE. Actually, studies have shown that those ICH patients who presents with an early onset, higher initial SBP, prior anti-thrombotic therapy, or milder neurological dysfunction at baseline were found to be associated with better functional outcomes in rapid SBP lowering (114,125,126). However, currently the characteristics of ICH patients benefiting from SBP control are still unclear and a complete screening scheme should be established to facilitate clinical practice in future studies.…”
Section: Intensive Blood Pressure-lowering Treatmentmentioning
confidence: 99%
“…None of these trials have shown a significant improvement in outcome although there is evidence of reduced hematoma expansion. The Factor VIIa in Acute Intracerebral Hemorrhage (FAST) trial showed reduced hematoma expansion over the first 24 hours 45 and a secondary analysis of the Intensive Blood Pressure Reduction in Acute Cerebral Haemorrhage Trials (INTERACT 1 and 2) found that blood pressure reduction reduced ICH plus IVH hematoma expansion 46 .…”
Section: Preventionmentioning
confidence: 99%
“…Based on available evidence, rapidly reducing blood pressure to 140-150 mmHg may likely balance the risk of hemorrhage expansion and cerebral autoregulation issues, although patients with higher presenting blood pressure (i.e. ≥ 180 mmHg) may have a greater risk of renal injury [30][31][32][33][34][35]. Knowledge of the patient's pre-ICH baseline blood pressures readings as well as frequent neurological assessments during hospitalization may help guide antihypertensive therapy and avoid further complications in the acute setting.…”
Section: Blood Pressure Managementmentioning
confidence: 99%